Pharmacogenetics and pharmacogenomics: The impact of the single nucleotide polymorphisms in drug response - Jančić Ivan; Arsenović-Ranin Nevena (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2015)
Individual variation in response to drugs is an important clinical problem, which ranges from failure to respond to the drug, over adverse reactions to drugs, to interactions among drugs being administered concurrently. Numerous findings indicate that the differences in the patients response on the same drug are caused by genetic variations. This is the subject of pharmacogenetics. Although pharmacogenetics generally equated with the concept of pharmacogenomics, pharmacogenetics is primarily related to variations in a single gene that influence the on drug response, while pharmacogenomics is a broader term, which studies how all of the genes (the genome) can influence responses to drugs. In focus of this paper will be individual variation in response to drugs arising from single nucleotide polymorphisms in genes encoding the drug target proteins, enzymes that metabolize drugs, drug transporters, and polymorphisms of genes responsible for toxicity and hypersensitivity to drugs. Determination of pharmacogenetic profile of patients could point out patients who are at increased risk of adverse drug effects (for which drug should be applied at lower doses or other drugs can be used) and those in which are likely to achieve the desired therapeutic effect, and so to enable individualization of therapy.